Bagaimana Perbedaan Kemampuan Literasi Matematika Siswa SMK dengan Tingkat Literasi Digital Tinggi dan Rendah dalam Menyelesaikan Soal Statistika Berbantuan Microsoft Excel - Dinda Masyita Putri Kurnia Dimmaja; Deka Anjariyah; Feriyanto Feriyanto (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to describe the mathematical literacy skills of vocational high school students in solving statistics problems with the help of Microsoft Excel based on digital literacy levels, which are grouped into high, medium, and low. The background of this study is based on the importance of mathematical literacy in dealing with everyday problems and the demands of the world of work, as well as the increasing need for digital literacy mastery in the information technology era. Both are essential competencies that support each other, especially in technology-based mathematics learning. The research approach used is descriptive qualitative with a purposive sampling technique, where the selection of subjects is based on the results of the digital literacy questionnaire, equivalence of mathematics scores, and adequate communication skills to support the interview process. The research instruments include a digital literacy questionnaire, a mathematical literacy test in the form of descriptive questions completed using Microsoft Excel, and interview guidelines that have been validated by experts. The data collection procedure was carried out through tests and in-depth interviews, while data analysis included the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate differences in students' mathematical literacy skills based on their digital literacy levels. Students with high digital literacy are able to master mathematical literacy indicators well, including communication, mathematization, problem-solving strategies, and reasoning and argumentation. They can optimally utilize Microsoft Excel features to present data, perform calculations, and draw logical conclusions. Students with moderate digital literacy demonstrate fairly good mastery, but still experience difficulties in aspects of problem-solving strategies and in-depth reasoning. Based on these findings, it can be concluded that digital literacy plays a crucial role in supporting students' mathematical literacy abilities.